The Use of Virtual Reality in Psychiatry: A Review - Kim, Suji; Kim, Eunjoo (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2020)
With the advancement in modern information technology, virtual reality (VR) is being increasingly used for the diagnosis, assessment, and treatment of mental disorders. Recently, a VR-based cognitive behavioral therapy for social phobia has been recognized as a new medical technology in South Korea. This might lead to an increase in the use of VR in the field of psychiatry. The present review provides an overview of the status of VR therapies in various psychiatric conditions such as anxiety disorder, post-traumatic stress disorder, psychosis, addiction, and eating disorder. Besides, it summarizes the role of VR therapy in the management of disorders associated with child and adolescence psychiatry as well as various other clinical applications. Additionally, we discuss the merits and limitations of VR therapy, which might serve as a useful reference for researchers. In the current environment wherein novel medical models consisting of a combination of digital devices and medicine are being developed; understanding new technologies such as VR could open new doors to mental health treatments.